Analisis Pemasaran Kelapa Sawit Rakyat Desa Perdomuan Nauli Kecamatan Kandis Kabupaten Siak Provinsi Riau - Marbun, Wika Srihartati; Puruhito, Dimas Deworo; Kurniawati, Fitri (Program Studi Agribisnis INSTIPER Yogyakarta, 2024)
Indonesia, as an agricultural country, has an agricultural sector that contributes significantly to the national economy. Palm oil is the main commodity that plays an important role in increasing state income, especially in Perdomuan Nauli Village, Kandis District, Riau. This research aims to analyze palm oil marketing in the village using descriptive methods. Primary data was obtained through interviews and questionnaires, while secondary data came from literature and related institutions. The research location was selected through purposive sampling involving 35 respondents who used three main marketing channels: Farmers–Collectors–RAM–PKS, Farmers–Collectors–PKS, and Farmers–RAM–PKS. The research results show that the Farmer–RAM–PKS channel provides the highest profits for farmers with a margin of IDR 434.3/kg, followed by the Farmer–Collector–PKS channel with a profit of IDR 234.3/kg. The Farmer–Collector–RAM–PKS channel, even though it is the longest, still provides profits for farmers of IDR 139.3/kg. Each channel has its own advantages and disadvantages, depending on the facilities provided and marketing costs incurred. This research emphasizes the importance of evaluating and improving marketing channels to increase the efficiency and welfare of oil palm farmers in Perdomuan Nauli Village